Odo Ya! Life With AIDS - Cypriano, Tania (United States, 1997)
An affirming story of how Candomblé, a Brazilian religion of African origin, has become a source of strength and power in the fight against AIDS in Brazil. Members of the community have pioneered Odô Yá!, an innovative HIV/AIDS education program. Shot in Rio de Janeiro, São Paulo and Bahia, the film shows the rituals of Candomblé and the celebration of Carnival. This lyrical documentary puts the epidemic in a cultural context, showing how a religion helps its followers cope with the illness, contrasting it with myopic government campaigns.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films